Computational studies of drugs for possible action against Covid-19 infections - Mishra, Ganesh Prasad; Panigrahi, Debadash (Journal of Drug Delivery and Therapeutics, 2020)
SARS-Cov-2 has emerged highly contagious viral infections so far and posed a global threat with significant human casualties and severe economic losses. There is urgent demand to develop rational therapies to control the drastic spread of the virus. Although there is no specific regimens are available to combat this pandemic situation so far. An attempt was made to perform Insilco studies of drugs applicable to respiratory tract infections with crucial SARS-COV-2 main protease (M-pro) enzyme. Insilco docking study was performed with Molegro Virtual Docker 5.5    on number of available medications of different categories specified for respiratory tract infections.Result indicates that Azithromycin, Dexamethasone and Remdesivir are highly effective and mainly interacted with key amino acid residues with hydrogen bonds and displayed excellent docking score -133, -141 and -153 kcal/mole respectively.This study advocates the possible use Azithromycin, Dexamethasone and Remdesivir drugs in combination to battle this pandemic condition. Further, this study will provide rationalized drugs and target for further in vitro and in vivo studies of SARS-CoV-2, new insights for those drugs currently ongoing clinical studies, and also possible new strategies for drug repositioning to treat SARS-CoV-2 infections.Keywords: Viruses, SARS-COV-2, Covid-19, Drugs, Computational docking Studies, Drug Design